2012
DOI: 10.1007/s00299-012-1266-4
|View full text |Cite
|
Sign up to set email alerts
|

Agroinfiltration of intact leaves as a method for the transient and stable transformation of saponin producing Maesa lanceolata

Abstract: We have developed a transformation protocol for saponin producing Maesa lanceolata. Using the protocol reported here, now we are able to generate the tools for the modification of saponin production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…1c). The A. tumefaciens strain has been shown to affect the efficiency of transient expression in grapevine (Zottini et al 2008), rose (Yasmin and Debener 2010), Maesa lanceolata (Faizal and Geelen 2012), and spinach (Cao et al 2017). In coffee, Mishra et al (2008) demonstrated that the Agrobacterium strain influenced the transient expression of uidA and gfp in embryogenic tissues.…”
Section: Effect Of the A Tumefaciens Strain On Transient Expression mentioning
confidence: 99%
See 1 more Smart Citation
“…1c). The A. tumefaciens strain has been shown to affect the efficiency of transient expression in grapevine (Zottini et al 2008), rose (Yasmin and Debener 2010), Maesa lanceolata (Faizal and Geelen 2012), and spinach (Cao et al 2017). In coffee, Mishra et al (2008) demonstrated that the Agrobacterium strain influenced the transient expression of uidA and gfp in embryogenic tissues.…”
Section: Effect Of the A Tumefaciens Strain On Transient Expression mentioning
confidence: 99%
“…In coffee, Mishra et al (2008) demonstrated that the Agrobacterium strain influenced the transient expression of uidA and gfp in embryogenic tissues. The virulence of Agrobacterium strains can be dependent on the target plant species (Faizal and Geelen 2012). This may be due to the ability of the bacteria to attach to plant cells or to differences in the T-DNA transfer mechanism (Wroblewski et al 2005).…”
Section: Effect Of the A Tumefaciens Strain On Transient Expression mentioning
confidence: 99%
“…Another study has been conducted on the transformation of Maesa lanceolata through Agrobacterium-infection in planta transformation for both transient and stable gene expression. It was concluded that optimum bacterial density (OD 600 nm = 1.0) significantly increased TE (Faizal and Geelen 2012). Trieu et al (2000) modelled a novel system of in planta transformation via seedlings infiltration in M. truncatula and argued that OD 600 nm of 1.6 was optimum for securing efficient TE, ranged from 2.9 to 27.6 %.…”
Section: Discussionmentioning
confidence: 98%
“…This result suggested that improvement of this process was effective. Indeed, improvement of T-DNA transfer increased stable transformation 46 47 . Inevitable, we focused on improvement of T-DNA transfer through new bred A. tumefaciens strain.…”
Section: Discussionmentioning
confidence: 99%